PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASIONAL, DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN (Studi Kasus pada Karyawan Bank bii Cabang Pemuda Kota Semarang) - Riski Eka Nanda, 10.05.51.0056; Liana, Lie (Students Journal of Economic and Management, 2014)
The purpose of this study was to examine the effect of leadership style, organizational commitment, and financial compensation to the employee at the employees performance bii Bank Youth Semarang. The population in this study were all employees / employee Youth Bii Bank city of Semarang. That amounts to 100 people. The results showed that partially contained significantly and positively influence between leadership style (X1) on the performance of the employee (Y); partial (individual) are significantly and positively influence the organizational commitment (X2) on the performance of the employee (Y); partial (individual) are significantly and positively influence the financial compensation (X3) on the performance of the employee (Y) and Leadership Style variable (X1), Organizational Commitment (X2), and the Financial Compensation (X3) simultaneously (together) the Employee Performance (Y).Keywords : Leadership style, Organizational Commitment, Financial Compensation, and Performance of the employee.